2017
DOI: 10.32598/ajnpp.4.3.79
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Educational Package Based on Visual-Spatial Processing in Reading Performance of Dyslexic Students

Abstract: Background: Dyslexia refers to a kind of learning difficulty, a combination of strengths and weaknesses which affects the reading and spelling learning process. Objectives: The aim of current research was to develop an instructional package based on visual spatial abilities and examine its efficacy on the reading performance of students with dyslexia. Materials and Methods: This is a quasi-experimental study with pre-test, post-test design and control group. The statistical population included dyslexic student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…Ortiz et al (3) reported the prevalence of this disorder to be 5 -12% using reading performance criteria cited in Peterson and Pennington (2012). Moreover, the prevalence of reading disorders among Iranian students was reported to be 4.58% (4). Considering the psychological and social consequences of the problems caused by differentiating children from normal children in children's lives (5), it is necessary to agree on a suitable solution based on research results.…”
mentioning
confidence: 99%
“…Ortiz et al (3) reported the prevalence of this disorder to be 5 -12% using reading performance criteria cited in Peterson and Pennington (2012). Moreover, the prevalence of reading disorders among Iranian students was reported to be 4.58% (4). Considering the psychological and social consequences of the problems caused by differentiating children from normal children in children's lives (5), it is necessary to agree on a suitable solution based on research results.…”
mentioning
confidence: 99%